The implications of alcohol mixed with energy drinks from medical and socio-legal standpoints - Sefen, Jessica Atef Nassef; Patil, Jayaditya Devpal; Cooper, Helen (Frontiers in Behavioral Neuroscience, 2022)
Co-ingestion of energy drinks and alcohol has long been in practice and has been poorly regulated despite a growing body of literature of their potential negative health impacts. Co-ingestion of energy drinks with alcohol has multiple counter-active effects such as reduction of body sway, fatigue and sedative effects induced by alcohol, along with increased subjective feeling of alertness, which may lead to increased binge-drinking, intoxication, decreased perception of intoxication, dehydration, and alcohol poisoning. Adding energy drinks to alcohol may also have synergistic effects in causing alcohol dependency and addiction. The association between caffeine, a common active ingredient in energy drinks, and alcohol is relatively well defined, however association with other active ingredients such as taurine, niacin, and pyridoxine, is less understood, pointing to a gap in our knowledge regarding this practice. Nonetheless, the current associations between AMED (Alcohol Mixed with Energy Drinks) and risky behavior secondary to intoxication and cases of alcohol poisoning have led various national governing bodies to regulate this practice. This review highlights the potential effects of AMED on human physiology based on what is known from human and animal models, and sheds light on specific biochemical interactions between alcohol and active ingredients found in energy drinks; Caffeine, Taurine, and Glucuronolactone. The review also touches on the regulation of this practice around the world, and the impact it has on its users, and points researchers to gaps in our knowledge on the interactions between alcohol and EDs and the full extent of their effects.